The Influence of Work Motivation and Leadership Style on Employee Discipline in the Environmental Management and Mining Support Unit - Robbi Hidayat; Marlina Widiyanti; Muhammad Yusuf; Muhammad Ichsan Hadjri (Journal La Bisecoman, 2024)
This study aims to determine the influence of work motivation and leadership style on employee work discipline in the environmental management and mining support work unit at PT Bukit Asam, Tbk. The population in this study is all employees in the environmental management and mining support work unit at PT Bukit Asam, Tbk in 2023 as many as 300 organic and outsourcing employees. The sample of respondents in this study became 172 organic and outsourced employees at PT Bukit Asam, Tbk with calculations using the slovin formula. The results of multiple linear regression analysis show that work motivation and leadership style have a positive and significant effect on work discipline. Work motivation, is expected to maintain good relations between fellow employees and superiors in one work team. Leadership style, the role of superiors needs to be evaluated in giving appreciation to employees, especially employees who provide good work results.